Toxoplasma gondii Toc75 Functions in Import of Stromal but not Peripheral Apicoplast Proteins. (2nd November 2015) - Sheiner, Lilach; Fellows, Justin D.; Ovciarikova, Jana; Brooks, Carrie F.; Agrawal, Swati; Holmes, Zachary C.; Bietz, Irine; Flinner, Nadine; Heiny, Sabrina; Mirus, Oliver; Przyborski, Jude M.; Striepen, Boris
Abstract : Apicomplexa are unicellular parasites causing important human and animal diseases, including malaria and toxoplasmosis. Most of these pathogens possess a relict but essential plastid, the apicoplast. The apicoplast was acquired by secondary endosymbiosis between a red alga and a flagellated eukaryotic protist. As a result the apicoplast is surrounded by four membranes. This complex structure necessitates a system of transport signals and translocons allowing nuclear encoded proteins to find their way to specific apicoplast sub‐compartments. Previous studies identified translocons traversing two of the four apicoplast membranes. Here we provide functional support for the role of an apicomplexan Toc75 homolog in apicoplast protein transport. We identify two apicomplexan genes encoding Toc75 and Sam50, both members of the Omp85 protein family. We localize the respective proteins to the apicoplast and the mitochondrion of Toxoplasma and Plasmodium . We show that the Toxoplasma Toc75 is essential for parasite growth and that its depletion results in a rapid defect in the import of apicoplast stromal proteins while the import of proteins of the outer compartments is affected only as the secondary consequence of organelle loss. These observations along with the homology to Toc75 suggest a potential role in transport through the second innermost membrane. Abstract : Protein targeting to plastids and mitochondria of parasites relies on an elaborate system of signals and machinery. We describe Toxoplasma and Plasmodium Toc75 and Sam50 proteins. TgToc75 is found to mediate stromal but not peripheral apicoplast protein import and to be essential for parasite growth and plastid maintenance.